Assessing the financial value of real-time energy trading services for privately owned non-commercial electric vehicles. (March 2020) - Meisel, Stephan; Merfeld, Tanja
Highlights: Shows that real-time trading services for e-vehicles are able to generate energy cost savings. Establishes a testbed for assessing and optimizing real-time trading services. Shows the impact of technology characteristics on the value of real-time trading services. Shows the impact of e-vehicle owner characteristics on the value of real-time trading services. Recommends policy measures for implementation of real-time trading services to stimulate e-vehicle adoption. Abstract: Real-time energy trading services for privately owned non-commercial electric vehicles are characterized by an e-vehicle provider, by a provider of energy trading skills and technology, and by the fact that the latter manages (dis-)charging of the e-vehicle of the former with real-time energy prices. We conduct a simulation study to present a comprehensive assessment of the financial value of such services. Such an assessment is required in order to provide policymakers with guidance on if and how real-time trading services can serve as a tool to incentivize e-vehicle ownership. We propose a fully reproducible simulation model of the value creation process of real-time trading services, and use the model to assess services with a range of e-vehicle provider characteristics as well as with a range of technology setups. Our empirical results show that all considered real-time trading services are able to create significant energy cost savings, and that overall cost savings strongly depend on technology characteristics, surcharge rate, as well as on the e-vehicle provider's commute, household size, and office hours. We show that services including solar energy generation have the largest economic potential but do not necessarily maximize renewable energy deployment with residential households. We conclude with recommendations for policymakers on how to tap the full economic potential of real-time trading services for stimulating the adoption of e-vehicles.